Computational studies demonstrating dithymoquinone of Nigella sativa as a potential anti-dengue agent: Short review - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier, 2024)
Dengue is acute tropical infectious illness, which is spread by mosquitoes, has presented a significant threat to public health worldwide. Unfortunately, there are no drugs that have been clinically proven to be effective at treating or preventing dengue. The development of some drugs is significantly hampered by our incomplete understanding of dengue pathogenesis. This short review provides a brief description of potential action against DENV of dithymoquinone to develop an anti-DENV inhibitor. In-vitro, in-vivo and clinical trials are required to establish the effectiveness and safety of dithymoquinone as an anti-dengue therapy, even though computational studies have demonstrated antiviral activity against DENV.